Cloning and Functional Characterization of the Polyketide Synthases Based on Genome Mining of Preussia isomera XL-1326 - Liu, Qingpei; Zhang, Dan; Xu, Yao; Gao, Shuaibiao; Gong, Yifu; Cai, Xianhua; Yao, Ming; Yang, Xiaolong (Frontiers in Microbiology, 2022)
Fungal polyketides (PKs) are one of the largest families of structurally diverse bioactive natural products biosynthesized by multidomain megasynthases, in which thioesterase (TE) domains act as nonequivalent decision gates determining both the shape and the yield of the polyketide intermediate. The endophytic fungus Preussia isomera XL-1326 was discovered to have an excellent capacity for secreting diverse bioactive PKs, i.e. the hot enantiomers (±)-preuisolactone A with antibacterial activity, the single-spiro minimoidione B with α-glucosidase inhibition activity, and the uncommon heptaketide setosol with antifungal activity, which drive us to illustrate how the unique PKs are biosynthesized. In this study, we first reported the genome sequence information of P. isomera. Based on genome mining, we discovered nine transcriptionally active genes encoding polyketide synthases (PKSs), Preu1-Preu9, of which those of Preu3, Preu4 and Preu6 were cloned and functionally characterized due to possessing complete sets of synthetic and release domains. Through heterologous expression in Saccharomyces cerevisiae, Preu3 and Preu6 could release high yields of orsellinic acid (OA) derivatives (3-methylorsellinic acid [3-MOA] and lecanoric acid, respectively). Correspondingly, we found that Preu3 and Preu6 were clustered into OA derivative synthase group by phylogenetic analysis. Next, with TE domain swapping, we constructed a novel “non-native” PKS, Preu6-TEPreu3, which shared very low identity with OA synthase, OrsA, from Aspergillus nidulans but could produce large amount of OA. In addition, with use of Preu6-TEPreu3, we synthesized methyl 3-methylorsellinate (synthetic oak moss of great economic value) from 3-MOA as the substrate, and interestingly, 3-MOA exhibited remarkable antibacterial activities, while methyl 3-methylorsellinate displayed broad-spectrum antifungal activity. Taken together, we identified two novel PKSs to biosynthesize 3-MOA and lecanoric acid, respectively, which kinds of such PKSs are rarely reported, and constructed one novel “non-native” PKS to largely biosynthesize OA. This work is our first step to explore the biosynthesis of the PKs in P. isomera, and it also provides a new platform for high-level environment-friendly production of OA derivatives and development of new antimicrobial agents.